Familiar quotations : a collection of passages, phrases, and proverbs traced to their sources in ancient and modern literature - Bartlett, John, 1820-1905.; Kaplan, Justin (Boston : Little, Brown, 1992)
The epitome of quotation books, Bartlett's began in 1855. More than 22,000 quotations are arranged chronologically by the birth date of the person quoted and there are extensive indexes by author, subject and keyword. Emphasis is on British and American quotations, with Bible and Shakespeare amply represented. Exact references to original sources and helpful historical footnotes are provided. Each edition deletes and adds quotations so it is wise to retain earlier copies. First published in 1855 as a small booklet containing a mere 258 pages of quotes by 169 authors, Bartlett's Familiar Quotations has been completely revised and updated for the sixteenth edition by noted Pulitzer Prize-winning biographer Justin Kaplan. Bartlett's gives the reader a vast panorama of the world, from the ancient Egyptians to the latest movie, from the inspirational to the downright funny. In addition to John Bartlett's original criterion that quotations be "household words", Mr. Kaplan has chosen quotes for their "literary power, intellectual and historical significance, originality, and timeliness". Bartlett's, unrivaled as the classic and indispensable reference, mirrors the culture and the changes that have taken place since 1980, when the fifteenth edition was published. It contains many non-traditional sources for quotations; new additions represent television, movies, politics, pop and rock music, advertising slogans, and even street slang. The sixteenth edition contains over 20,000 quotations, representing 2,550 authors, 340 of whom are new to Bartlett's. Although Shakespeare and the Bible are still the most heavily quoted sources, this new edition casts a wider net than its predecessors in broadening Bartlett's cultural base. Newcomers include Russell Baker, Leonard Bernstein, Mel Brooks, Noam Chomsky, Annie Dillard, Elvis, M.F.K. Fisher, Stephen Hawking, Milan Kundera, John Lennon, Norman Mailer, Nelson Mandela, Salman Rushdie, Dr. Seuss, Sun-Tsu, the Talmud, Alice Walker, and Elie Wiesel. Mr. Kaplan, with the assistance of a number of scholars and the Little, Brown editorial staff, has given even the mainstays of Bartlett's close scrutiny. Not only has the general text been considerably revised, the supplementary information in the footnotes has been thoroughly edited and pruned. Several quotations that were formerly in the footnotes have been moved to the main text. In the famous Bartlett's tradition, authors are arranged in chronological order, which illuminates the prevailing influences and ideas surrounding any given quotation. The general index, more than 600 pages long, continues to be an invaluable resource for finding quotations by way of keywords; it has been painstakingly edited to be more accurate and complete. Whether for sheer enjoyment or literary pursuit, for inspiration or adding zest to conversation or a presentation, for research or for the ultimate source for "Who said that", this new edition of Bartlett's is a map through our culture and history.
Includes bibliographical references and indexes.
Keywords: Quotations, English; Literature -- Aphorisms and Proverbs; Quotations